(untitled) (Bangladesh Pharmaceutical Journal, 2012)
Diabetes is classified as a metabolic disorder manifested by elevated level of glucose in the blood. An attempt has been made to compare the antidiabetic activity of hexane extract of lemon peel (Citrus Limon) with that of a marketed product, glimepiride, in alloxan-induced diabetic rats. The study was performed by the measurement of blood glucose level using a glucometer. It was found that the hexane extract of lemon peel showed antidiabetic activity comparable to that of glimepiride. It can thus be inferred that the extract of lemon peel possesses significant antidiabetic activity. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12577 Bangladesh Pharmaceutical Journal 15(2): 131-134, 2012